Current Situation, Existing Problems and Prospect of the Study of Social Stratification in Contemporary China - Zhang Hailun; L. A. Lebedintseva (Дискурс)
Introduction. Under the backdrop of market economy and social transformation in China, the class structure of society has undergone profound changes, and the traditional class division is no longer relevant. However, there are still some unresolved problems in the study of social strata in China. The lack of diversity and comparability of research methods limits the depth and scope of research. Relatively few studies have been conducted on some emerging classes. Research on the relationship between social class and other social issues is insufficient, such as the relationship between class and education, class and income distribution, etc., are still limited.   Methodology and sources. At present, a social classification model has been proposed to study social stratification in China, taking into account the characteristics of China's national conditions. A large number of empirical studies have revealed the evolution and characteristics of China's social class structure. The mechanism of social class formation and the factors influencing them have been studied, which has provided theoretical support for social development. Modern stratification models of Chinese authors have been used for the analysis in comparison with traditional models.   Results and discussion. The study of social stratification in China inherited the theoretical framework and empirical research methods of Western social scientists, and there are also attempts to develop its own model of social stratification in combination with the actual situation in China. The structure of social stratification in China is characterized by the need to take into account the state redistribution system and the market economy model. However, there is a consensus that government officials are at the top of the social hierarchy, and the class of peasants and unemployed are at the bottom of society; mental workers (white collars) are higher than manual workers (blue collars). The results of studies on the impact of human capital on social stratification show that gender and educational level have universal significance in society; household registration system and housing type are special independent variables that affect social stratification in China more than in other countries, etc. However, there is a lack of relevant empirical studies that could provide specific quantitative data showing how independent variables affect social stratification in China. Many new social and professional groups have emerged in Chinese society. In recent years, some Chinese scholars have studied such specific social and professional groups, the most widespread and in demand in the labor market in China, taking into account the digitalization processes.   Conclusion. It is necessary to further explore the methods and models of social stratification suitable for China's national conditions so as to cover the characteristics of social class diversity. It is necessary to strengthen the research on the relationship between social class and other social issues so as to provide more effective policy recommendations for social development. It is also necessary to strengthen the research on emerging classes, pay attention to their social status, mobility and responsibilities, and provide more effective support and guidance for their development.